2020
DOI: 10.1093/cercor/bhaa381
|View full text |Cite
|
Sign up to set email alerts
|

Cortical Gyrification Morphology in Individuals with ASD and ADHD across the Lifespan: A Systematic Review and Meta-Analysis

Abstract: Autism spectrum disorder (ASD) and attention-deficit hyperactivity disorder (ADHD) are common neurodevelopmental disorders (NDDs) that may impact brain maturation. A number of studies have examined cortical gyrification morphology in both NDDs. Here we review and when possible pool their results to better understand the shared and potentially disorder-specific gyrification features. We searched MEDLINE, PsycINFO, and EMBASE databases, and 24 and 10 studies met the criteria to be included in the systematic revi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 88 publications
2
9
0
Order By: Relevance
“…Importantly, we found no significant between-group differences in l GI in school-aged children and adolescent youth. This is in agreement with the results of our recent systematic review and meta-analysis of previous ASD and ADHD gyrification studies ( Gharehgazlou et al. 2020 ) suggesting that the null findings were not the result of identified limitations.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Importantly, we found no significant between-group differences in l GI in school-aged children and adolescent youth. This is in agreement with the results of our recent systematic review and meta-analysis of previous ASD and ADHD gyrification studies ( Gharehgazlou et al. 2020 ) suggesting that the null findings were not the result of identified limitations.…”
Section: Discussionsupporting
confidence: 93%
“…A limited number of studies have examined gyrification morphology in ASD and ADHD with contradictory results, possibly due to small sample sizes among other limitations ( Gharehgazlou et al. 2020 ).…”
Section: Introductonmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study demonstrated that leptin is also associated with the emergence of inhibitory function of GABAergic neurons (79). Given the repeated observations of altered cortical structures (80)(81)(82), reduced white matter integrity (83,84), and excitatory/inhibitory imbalance (85,86) in ASD, it seems plausible to assume that leptin levels at birth play an important role in ASD etiopathology.…”
Section: Discussionmentioning
confidence: 99%
“… 1 However, the results of these studies have been inconsistent and usually not replicable. 1 2 To date, there is not a single neuroimaging marker for ADHD diagnosis.…”
mentioning
confidence: 99%